Petrography, mineralogy and trace element chemistry of Yamato-86029, Yamato-793321 and Lewis Cliff 85332: Aqueous alteration and heating events - Tonui,Eric; Zolensky, Michael; Lipschutz, Michael (National Institute of Polar Research, 2002)
P(論文) We have examined mineral grains and matrix of new Antarctic carbonaceous chondrites Yamato (Y)-86029,Lewis Cliff (LEW) 85332 and Yamato (Y)-793321 for evidence of parent body aqueous alteration and heating events. Y-86029 and LEW 85332 are unique carbonaceous chondrites with unusual textures. Y-86029 is the second thermally metamorphosed CI chondrite recovered from Antarctica. It is characterized by destruction of preexisting anhydrous silicates during aqueous alteration accompanied by formation of carbonates, which together with the phyllosilicates were subsequently heated at metamorphic temperatures of at least 500-600℃. The carbonates are now present as Fe-rich drusy aggregates and giant periclase clasts and globules that have rarely been encountered in carbonaceous chondrites. LEW 85332 is an unequilibrated and highly brecciated type-3.0-3.1 chondrite that shows no clear evidence of alteration of chondrules or matrix silicate grains. However, matrix phyllosilicates underwent extensive aqueous alteration and subsequent dehydration by moderate thermal metamorphism (at least 500-600℃). This suggests that the formation of hydrous phases and subsequent heating occurred prior to final accretion in the parent body. Y-793321 is a CM2 chondrite that contains a variety of clasts exhibiting varying degrees of aqueous alteration. Petrographic evidence of thermal metamorphism in Y-793321 is only limited to a few phyllosilicate clasts in the matrix. The presence of tochilinite, carbonates and partially dehydrated phyllosilicates suggests that it experienced very mild thermal metamorphism. RNAA data based on 15 thermally mobile trace elements confirm the severity of open-system heating as Y-793321<500℃<LEW 85332<Y-86029≤700℃. It is conceivable that Y-793321 experienced retrograde aqueous alteration after thermal metamorphism but no unambiguous evidence for this is present. departmental bulletin paper